2004
DOI: 10.1016/s0378-1097(04)00018-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the new T-cell-stimulating antigens fromMycobacterium tuberculosisculture filtrate

Abstract: The proteins secreted by Mycobacterium tuberculosis are an important target for vaccine development. To identify the antigens from M. tuberculosis culture filtrate (CF) that strongly stimulate T-cells, the CF was fractionated by ion-exchange chromatography and then nonreducing sodium dodecyl sulfate^polyacrylamide gel electrophoresis with mini-whole gel elution. Each fraction was screened for its ability to induce interferon-gamma (IFN-Q) production in peripheral blood mononuclear cells isolated from healthy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…MTSP14 (Rv1827), a mycobacterial protein described as a T-cell antigen in this study and in a previous study by Lim et al (30), should be considered the same protein as CFP17 identified by Weldingh et al (55). Evaluation of purified polypeptides for recognition by PFMCs of tuberculosis pleuritis patients.…”
Section: Isolation Of Culture Filtrate Proteins Of M Tuberculosis H supporting
confidence: 72%
“…MTSP14 (Rv1827), a mycobacterial protein described as a T-cell antigen in this study and in a previous study by Lim et al (30), should be considered the same protein as CFP17 identified by Weldingh et al (55). Evaluation of purified polypeptides for recognition by PFMCs of tuberculosis pleuritis patients.…”
Section: Isolation Of Culture Filtrate Proteins Of M Tuberculosis H supporting
confidence: 72%
“…Multiple studies provide evidence that antigens recognized by the protected group, but not active TB patients, can be considered for vaccine development strategies by using IFN-␥ response as a protective correlate (29 -31). Although donor to donor variation exists in antigen recognition and magnitude of response, this approach is considered a highly viable method to identify the protective antigens (28). In agreement with a previous study (32), healthy contacts in our study displayed a strong IFN-␥ response to the 2D LPE fractions as compared with that of TB patients.…”
Section: Discussionsupporting
confidence: 91%
“…Like many previous T cell antigen discovery efforts (15,16,28), we focused on the secreted proteins of M. tuberculosis. However, our current efforts differ from earlier studies, which used experimental animals (15), whereas our study aims at immunological responses to human TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel vaccines are required for a variety of infectious diseases, including tuberculosis, for which no truly efficacious vaccine has yet been designed (16). A number of antigens have been considered for developing new tuberculosis vaccines (3,19,33). Early secreted antigenic target 6-kDa protein (ESAT-6) is found in Mycobacterium bovis and Mycobacterium tuberculosis but not in the vaccine strain Mycobacterium bovis BCG (12).…”
mentioning
confidence: 99%